Evaluating strategies for global respiratory pandemic control at ports: a modelling study - Gregory Gan; Jue Tao Lim; Tong Guan; Sharon Esi Duoduwa; S Balakumar; Janhavi A; Borame L Dickens (BMJ Public Health)
Background Heavy reliance on container shipping during the COVID-19 pandemic with lockdown implementation and air travel bans placed substantial pressure on shipping crews and ports. Long waiting times at ports, substantial economic losses and massive supply chain disruption of essential and medical goods were observed. To minimise this for future pandemic preparedness, we explore the use of quarantining and testing of crews preboarding instead of quarantining at port calls or during voyages.Methods Using a microsimulation model of 10 000 vessels and 300 000 crew, we examine the effectiveness of nine predeparture control strategies in reducing COVID-19 outbreak sizes, from no control to the use of 7-day and 14-day quarantining, and addition of polymerase chain reaction (PCR) or antigen rapid test (ART) testing. To assess different infection parameters, we explored three variants (Alpha, Delta and Omicron), four prevalences (0.1%, 0.5%, 1% and 2%) and three quarantine compliances (50%, 90% and 100%).Results Across the prevalences with no intervention, our modelled simulations estimate that approximately 3%, 15%, 28% and 47% of crews are infected, totalling around 9400, 44 900, 82 600 and 141 300 infections. At 2% prevalence, averaged across variants and compliances, when 7-day predeparture quarantining (7DQ) is introduced, 23 900 (range: 21 500–25 200) estimated cases are averted, rising up to 40 900 (40 200–41 600) for 14DQ. With additional predeparture PCR testing, this increases further to 102 100 (100 100–104 500) and 106 800 (106 100–108 100) respectively. Should ART testing be used instead, 92 600 (92 200–93 200) and 100 000 (98 900–101 100) estimated cases are averted. The use of predeparture PCR testing and PCR testing 1 week before departure has the greatest reduction at 108 200 (106 400–110 600) and 111 600 (110 500–113 000).Conclusion In our simulation model, we show that preboarding control measures can be effective in limiting outbreaks, reducing the number of active cases on marine vessels without access to adequate medical care while simultaneously reducing port congestion and facilitating for the greater global transport of essential goods.